2016
DOI: 10.4102/phcfm.v8i2.959
|View full text |Cite
|
Sign up to set email alerts
|

University of Venda’s male students’ attitudes towards contraception and family planning

Abstract: BackgroundMany young men continue to disregard the importance of contraception and family planning in South Africa. The fact that even university students also do not take contraception and family planning seriously poses a serious threat to their own health and well-being.AimThis paper aims at investigating the attitudes of male students towards contraception and the promotion of female students’ sexual health rights and well-being at the University of Venda.MethodsQuantitative research method is used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…A higher proportion of females were because the majority of the nurses were females (84.1%). Significantly higher knowledge of female participants in many questions as observed in this study is similar to Raselekoane NR (2016) study, who reported a non-serious approach of the male students towards contraception and family planning [37]. Gender differences should not be ignored during medical education to avoid compromise with the sexual and reproductive health rights of the clients [38].…”
Section: Discussionsupporting
confidence: 84%
“…A higher proportion of females were because the majority of the nurses were females (84.1%). Significantly higher knowledge of female participants in many questions as observed in this study is similar to Raselekoane NR (2016) study, who reported a non-serious approach of the male students towards contraception and family planning [37]. Gender differences should not be ignored during medical education to avoid compromise with the sexual and reproductive health rights of the clients [38].…”
Section: Discussionsupporting
confidence: 84%
“…For instance, the regular usage of family planning among sexually active, single undergraduate students at a tertiary institution in Kano State, Nigeria, was low (15.63%), [23] and only 38.0% of the University of Venda's (South Africa) male students reported correctly using a method for preventing pregnancy. [25] This confirms that awareness and knowledge of contraceptive methods do not necessarily translate to the use of contraception.…”
Section: Discussionmentioning
confidence: 62%
“…These findings of this study indicated that the knowledge and awareness of birth control of pharmacy students at LHU were lower than the rates reported in other studies in Malaysia, [14] Nigeria, [23,24] and South Africa. [25] However, increasing levels of awareness can be attributed to the increasing use of social networks/media, which was identified as one of the main sources of knowledge in this study. This finding is consistent with other studies that identified the internet and social media as the greatest sources of health-related information for undergraduate students.…”
Section: Discussionmentioning
confidence: 78%
“…The university students at the institution engage in unprotected sex, putting themselves at risk of HIV infection as confirmed by different studies conducted at the university [31,32]. Also, regular student reproductive health statistics at the university suggest there is an increase of STIs(60%), HIV infections(100%), termination of pregnancies(32%) referrals(40%) and unplanned pregnancies(60%)in the last five years [33]. Furthermore, a recent study at the University of Venda suggests that male students have a negative attitude towards contraceptives, such as condoms, and they did not use them [34].…”
Section: Introductionmentioning
confidence: 88%